Āʼīn-i Jammūṉ va Kashmīr : jaisā kih ise Jammuṉ va Kashmīr Āʼīn Sāz Asamblī ne pās kiyā (Dāʼirakṭoreṭ āf Infārmeshan, Jammūṉ va Kashmīr, 1956)
Laws and statutes for Jammu and Kashmir State as passed in 1956.